Argometer Becak Motor Berbasis Android - Muhammad Rezky; Muldi Yuhendri (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
Motorcycle pedicab is one of the land transportation vehicles that are still widely used by the community, especially for short distances. One of the disadvantages of using a motorcycle pedicab for transportation is the unavailability of standard fare for passengers. In this paper, a taximeter is proposed to determine motorcycle pedicab rates based on distance traveled. The taximeter display in the form of mileage and rate is designed using the Android application and Arduino Uno as data processing. This device is equipped with a hall effect sensor as a reader of wheel rotation and a bluetooth module as the interface between Android and Arduino. In addition, the Android screen also provides a start and stop button to start or stop the calculation of the meter. The experimental results show that this devices have worked in accordance with the objectives, where the android screen has been able to display distance data and pedicab rates according to mileage.